Multicenter Evaluation of Two Next-Generation HIV-1 Quantitation Assays, Aptima Quant Dx and Cobas 6800, in Comparison to the RealTime HIV-1 Reference Assay - Wiesmann, Frank (J Clin Microbiol, 2018)
High accuracy and precision at the lower end of quantification are crucial requirements of a modern HIV viral load (VL) assay, since some clinically relevant thresholds are located at 50 and 200 copies/ml. In this study, we compared the performance of two new fully automated HIV-1 VL assays, Aptima HIV-1 Quant Dx and Cobas HIV-1 (Cobas 6800), with the established RealTime m2000 assay. Assay precision and accuracy were evaluated in a retrospective evaluation out of excess plasma material from four HIV-1+ individuals (subtypes B, C, CRF01_AE, and CRF02_AG). Native plasma samples were diluted to nominal concentrations at 50 and 200 copies/ml (according to the RealTime m2000 assay). All dilutions were tested in triplicate in five independent runs over 5 days and in three labs per system. Assay concordance was determined using 1,011 surplus clinical routine samples, as well as selected retrospective longitudinal samples from 7 patients on treatment. The three assays yielded highly concordant results for individual clinical samples (R(2) > 0.98; average difference, ≤0.2 log copies/ml) and retrospective longitudinal samples from patients on treatment. The Aptima and RealTime assays showed similar high precision, meeting the 5σ criterion for the majority of samples across all labs and subtypes. The Cobas assay was less precise, missing the 5σ criterion for the majority of samples at low concentrations. In this analysis, results from the Cobas assay appeared less reliable near the clinically relevant cutoff and should be interpreted with more caution in this context. Due to high precision, full automation, and high concordance with the RealTime assay, the Aptima assay represents a good alternative in routine VL monitoring.